Genesis of adaptation processes of foreign students in Ukraine - Severyn, N.; Severyn, V.; Lapuzina, O. (Problems of Engineer-Pedagogical Education, 2021)
The article is devoted to the research of the topical problem of the adaptation of international students in Ukraine. In the modern multicultural world international cultural, educational, economic and political relations are intensively developing. The scientific, cultural, economic elites of different countries are converging and cultures are interpenetrating. This leads to an increase in the social significance of foreign languages in the development of the modern personality and society. There is a growing need for fast and high-quality learning of a foreign language, including Ukrainian as a foreign language. Getting an education in a foreign country is accompanied by a number of problems, one of which is the social and cultural environment adaptation. The stage of pre-university training plays a major role in the further education of international students in Ukrainian universities, so the problem of adaptation at this stage is the most important. The task of teachers is to make cultural, linguistic, psychological and social adaptation successful. It should contribute to the quality of the learning process at the main faculties in the chosen specialty, and also to the formation of the personality of the future specialist. The article highlights the types of work with international students that help to soften and accelerate their adaptation to the new educational, linguistic, social and cultural environment. Extracurricular work has an important role. There are excursions, culture trips, visits to museums, theaters, philharmonic halls, sports competitions, contests, trips to other cities of Ukraine, etc. It helps to relieve stress from meeting a new culture and education system, to bring together representatives of different countries and cultures. Coordination of actions of teachers of different education institutions is also dominant in creating comfortable educational conditions and contributes to the successful adaptation of international students to the cultural and educational space of Ukraine. In the future, it is planned to create a Center for Intercultural Communication of Foreign Students at the Faculty of International Education of the National Technical University "Kharkiv Polytechnic Institute", which will help to reveal the creative abilities of international students and get acquainted with the original Ukrainian culture. The activities of the Center will help to form a comfortable social-psychological environment, to cultivate a tolerant attitude towards representatives of other cultures and religions through the participation of students in multinational group activities.